Value of electrocardiographic screening for the early diagnosis of arrhythmic and malignant heart disease in pediatric age. (24th May 2021) - Leoni, L; Elhyka, A; Ferretto, S; Fumanelli, J; Cerutti, A; Di Salvo, G
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The 12-lead electrocardiogram (ECG) is an instrument that can identify cardiac conduction system abnormalities that predispose to sudden cardiac death (SCD) in completely asymptomatic subjects. The rate of sudden cardiac death in pediatric age is estimated to be around 1-1.5 cases per 100.000 individuals, and 10-15% of events occur during physical activity. We evaluated the importance of the electrocardiogram performed in pediatric age in the early detection of asymptomatic electrocardiographic alterations, suggestive for the presence of electrical or structural heart disease potentially at risk for sudden death. Materials and Methods: We analyzed 623 patients between 0 and 16 years of age who were sent to the second level pediatric arrhythmology clinic in Padua Hospital between October 2013 and March 2020. The patients were redirected at our clinic after a first finding of electrocardiographic alterations, following ECG performed before the beginning of sport activity, suspected of life-threatening pathologies. The following parameters were evaluated of all patients: clinical suspect of sending the pediatric arrhythmology clinic and electrocardiogram. Then, depending on the type of pathology suspected, the following diagnostic tests were carried out to confirm the clinical suspicion, and if confirmed, to carry out an adequate risk stratification: Holter ECG, ergometric Results: Among the evaluated population (623 patients), 393 patients (63%) were sent to the pediatric arrhythmology clinic by sports medicine, 179 (29%) were sent by clinical o family pediatrician, and 51 patients (8%) were sent after ECG performed at hospital facilities for familiarity. The majority, 280 patients (45%), were sent for suspected WPW; 124 patients (20%) were sent for BEV and suspected ARVD; 85 patients (14%) for suspected long QT, 31 patients (5%) for suspected Brugada Pattern; 7 patients (1%) suspected CPVT; 8 patients (1%) for electrocardiographic changes with suspected HCM; 1 patient (0.01%) suspected shortened QT, and 88 patients (14%) for other arrhythmic disorders not at risk of sudden death. The diagnosis of WPW was confirmed in 280 patients, LQTS in 45 patients, SQTS in 1 patient, S. di Brugada in 8 patients, CPVT in 5 patients, HCM in 8 patients and ARVD in 6 patients. Conclusions: Our study shows that the electrocardiographic screening already in pediatric age allows the diagnosis and subsequent early treatment of life-threatening arrhythmic heart diseases.